Cartilage oligomeric matrix protein enhances the vascularization of acellular nerves - Wei-ling Cui; Long-hai Qiu; Jia-yan Lian; Jia-chun Li; Jun Hu; Xiao-lin Liu (Neural Regeneration Research, 2016)
Vascularization of acellular nerves has been shown to contribute to nerve bridging. In this study, we used a 10-mm sciatic nerve defect model in rats to determine whether cartilage oligomeric matrix protein enhances the vascularization of injured acellular nerves. The rat nerve defects were treated with acellular nerve grafting (control group) alone or acellular nerve grafting combined with intraperitoneal injection of cartilage oligomeric matrix protein (experimental group). As shown through two-dimensional imaging, the vessels began to invade into the acellular nerve graft from both anastomotic ends at day 7 post-operation, and gradually covered the entire graft at day 21. The vascular density, vascular area, and the velocity of revascularization in the experimental group were all higher than those in the control group. These results indicate that cartilage oligomeric matrix protein enhances the vascularization of acellular nerves.